Pendampingan Dalam Mengembangkan Usaha Air Bersih Syariah Yang Berkelanjutan Dan Berkeadilan - Muslim; Sarwono; Ria Astuti Safitri; Pini Susanti; Susilo (Gotong Royong, 2025)
Clean water is a fundamental human need that plays a vital role in supporting public health, welfare, and the socio-economic sustainability of communities. However, in Pematang Rahim Village, Mendahara Ulu District, the management of the Community-Based Drinking Water Supply System (SPAM) still faces various challenges, particularly in aspects of governance, transparency, and the application of justice principles. This community service program aims to strengthen SPAM governance based on Sharia principles through a Community-Based Participatory Action (CBPA) approach, which places the community as the main actor in every stage of activity. The program was implemented in four stages: identifying needs and problems, providing education and training on Sharia principles in social enterprises, offering hands-on assistance in drafting Sharia-based governance documents, and conducting monitoring and evaluation. The results show significant improvements in several areas. Participants’ understanding of Sharia principles increased to 90%, especially regarding the concepts of justice, trust (amanah), and partnership contracts such as musyarakah and mudharabah. Financial transparency and accountability improved by 75% through the implementation of a simple reporting system and collective deliberation mechanisms. Community participation in decision-making and supervision increased by 70%, while institutional strengthening through the formation of the Sharia SPAM Management Team rose by 80%, reflecting stronger independence and commitment to sustainability. Overall, the implementation of Sharia principles in SPAM governance not only enhances managerial capacity and institutional transparency but also fosters moral, social, and spiritual values oriented toward justice, sustainability, and the well-being of rural communities.